2014
DOI: 10.19173/irrodl.v15i1.1665
|View full text |Cite
|
Sign up to set email alerts
|

Student satisfaction with a web-based dissertation course: Findings from an international distance learning master's programme in public health

Abstract: <p><strong>Introduction</strong></p><p>Online distance learning (e-learning) is now an established method for providing higher education, in the UK and across the world. The focus has largely been on developing the technology, and less attention has been given to developing evidence-informed course provision. Thus the effectiveness of this teaching approach, and its acceptability to students, is, at times, uncertain. Many higher education courses require students to submit a disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
1
15
0
3
Order By: Relevance
“…Croxton (2014) reviewed literature through the lens of Bandura's social cognitive theory, Anderson's interaction equivalency theorem, and Tinto's social integration theory regarding presences in online course design. Croxton noticed, as Spears did (2012), that teaching presence served as a very significant factor that influenced student satisfaction and persistence in online learning (Estelami, 2012;Harrison, Gemmell, & Reed, 2014;Kranzow, 2013). The review by Croxton was uncertain about student satisfaction and course satisfaction, both of which have their own components (Arbaugh, 2000;Artino, 2008, Gunawardena & Zittle, 1997Keeler, 2006;Lee et al, 2011) and further caution is needed in understanding and interpreting the relationship between teaching presence and satisfaction.…”
mentioning
confidence: 95%
“…Croxton (2014) reviewed literature through the lens of Bandura's social cognitive theory, Anderson's interaction equivalency theorem, and Tinto's social integration theory regarding presences in online course design. Croxton noticed, as Spears did (2012), that teaching presence served as a very significant factor that influenced student satisfaction and persistence in online learning (Estelami, 2012;Harrison, Gemmell, & Reed, 2014;Kranzow, 2013). The review by Croxton was uncertain about student satisfaction and course satisfaction, both of which have their own components (Arbaugh, 2000;Artino, 2008, Gunawardena & Zittle, 1997Keeler, 2006;Lee et al, 2011) and further caution is needed in understanding and interpreting the relationship between teaching presence and satisfaction.…”
mentioning
confidence: 95%
“…In addition to that, Unal (2011), who has evaluated Erasmus student mobility program with CIPP model, has reached the conclusion that students have positive opinion about the program. Harrison et al (2014) has evaluated the graduate curriculum which is conducted with distance education and has reached the conclusion that the opinions of the students about the curriculum are positive. Therefore, the studies mentioned above do not show parallelism with the results of this study, which reached the conclusion that opinions of the students are gathered around "I neither agree nor disagree" about the distance education curriculum of the Foreign Language I course.…”
Section: Discussion On the Students' Opinions About Distance Educatimentioning
confidence: 99%
“…Lambrinidis' (2014) study has shown that integrating video clips, synchronous online tutorials and online discussion groups in e-learning facilitate the use of interactive learning materials, increase its intelligibility and create a stronger bonds between students, teachers and learning material. Harrison, Gemmell, and Reed (2014) have found that postgraduates who use only e-learning as the main method are, in general, content with their studies. Thus, this method can become a priority in the second cycle studies.…”
Section: Discussionmentioning
confidence: 99%